Perencanaan Check Dam Penampung Sedimen Di Sungai Jepara Kecamatan Way Jepara Kabupaten Lampung Timur - Nainggolan, Susi Suryanta; Susilo, Gatot Eko; Perangin - Angin, Geleng (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Jepara watershed is part of the watershed is located in East Lampung district with an area of 10 km 2 , where Jepara River is one of river flowing into Lake Jepara. Jepara River conditions at this time had a reduction in the flow of flood discharge due to reduced cross-sectional area of the river due to sedimentation. The main cause of the high rate of sedimentation is the destrusction of water catchment areas and land management less attention to the principles of conservation land. Therefore it is very necessary management effective river drainage area with emphasis on the conservation and protection of the land and water, especially in the upper reaches of the river. One of the measures for erosion and sedimentastion problem in this river is by building sediment control structures or so-called check dams. From the calculations have been done check dam is planned to have the following physical; lighthouse spillway crest elevation checkerboard on +35,915 m elevation with an effective height of 3 m and a depth of 2,5 m foundation,wide spillway lighthouse checkerboard obtained by 40 m, Q design with a return period of 50 years at 119,9113 m3/sec, high wing checkerboard of 2,007 m in elevation +39,622 with a height of 0,6 m surveillance, construction of the main dam is a concrete construstion, lighthouse spillway crest elevation of the sub dam +33,915 m with a heigt of 1 m and a lighthouse foundation depth of 1,2 m, a high wing sub dam at 1,9 m an elevation of + 34,4251 m with a height of 1,0 m surveillance, construction of the sub dam is a concrete construstion,the elevation of the floor protected at +32,915 m elevation with a thickness of 0,5 m, the construction of a concrete construstion. Keywords : Jepara River, erosion, sedimentation, checkdam